2021
DOI: 10.1108/jabs-05-2021-0179
|View full text |Cite
|
Sign up to set email alerts
|

Green recovery strategies for the mining industry of India: lessons learned from the COVID-19 pandemic

Abstract: Purpose This study aims to find and evaluate the impact of COVID-19 in India’s mining activities. From the literature survey and input from experts, 14 important factors and ten green recovery strategies are identified. These 14 factors and 10 strategies are examined in a real industrial environment. Design/methodology/approach In this research study, fuzzy-complex proportional assessment is used to compare the identified strategies with the selected factors. Based on the outcome, this study identifies the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 66 publications
0
18
0
Order By: Relevance
“…Shcherbakova et al (2019) note the level of adaptation at (r=0.52; p<0.01) and link it with the influence of external factors, such as social pressure, the influence of parents. In turn, Marimuthu et al (2021) show the high correlation between the level of resilience and the degree of adaptation of the individual to changes in the social environment.…”
Section: Discussionmentioning
confidence: 99%
“…Shcherbakova et al (2019) note the level of adaptation at (r=0.52; p<0.01) and link it with the influence of external factors, such as social pressure, the influence of parents. In turn, Marimuthu et al (2021) show the high correlation between the level of resilience and the degree of adaptation of the individual to changes in the social environment.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, this special issue published seven articles in the area of sustainable recovery in supply chains. The first article analyzed different strategies for green recovery in the context of the mining industry of India and found that strategies for eco-innovation practices, environmental awareness and education and training are the three primary strategies for green recovery (Marimuthu et al , 2021). The second article explored 13 critical sustainable recovery measures for transportation systems and found that efficient traffic management, sustainability-focused policies, sensitization of stakeholders, financial support and adoption of 4 R practices are important for a sustainable recovery in freight transportation systems (Dwivedi et al , 2021).…”
Section: Green Recovery Through Sustainable Supply Chains: Implicatio...mentioning
confidence: 99%
“…The pandemic has arisen various issues regarding environmental sustainability and confronted various measures taken by the industrial sector toward achieving overall sustainability. To this theme, Marimuthu et al (2021) contributed to exploring the attention that must be taken when addressing COVID-19 and sustainability issues in India’s mining sector by identifying 14 significant repercussions of the outbreak and 10 green recovery solutions. However, the issues regarding sustainability are apparent in India even before the occurrence of the outbreak.…”
Section: Literature Reviewmentioning
confidence: 99%
“…C4. Reduced consumption pattern (Bakalis et al , 2020; Eggers, 2020; Ivanov, 2020b; Javaid et al , 2020; Knight et al , 2020; Marimuthu et al , 2021) – As a consequence of economic recession induced by the pandemic outbreak, income and revenue of the individuals have been declined. Moreover, due to lockdown measures, people’s movement has been ceased and forced to be in-home throughout, enabling a confined use of only essential products and consequently reducing the demand for ancillary products.…”
Section: Model Developmentmentioning
confidence: 99%